Calcipotriene/betamethasone dipropionate foam: primary evidence supporting its use in patients with psoriasis vulgaris. A narrative review - Narbutt, Joanna; Czajkowski, Rafał; Lesiak, Aleksandra; Owczarek, Witold; Reich, Adam; Szepietowski, Jacek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Psoriasis vulgaris is a chronic, immune-mediated disorder, which has a substantial impact on all aspects of patients’ quality of life. In most patients, the disease is mild to moderate and is successfully treated with topical agents. The most common therapy involves a vitamin D3 analogue (calcipotriene) in combination with a synthetic corticosteroid (betamethasone dipropionate). The aerosol vehicle (foam) with softening properties is another formulation of this combination drug, apart from ointment and gel, expanding the therapeutic options available to patients with psoriasis. The article describes the pharmacokinetic and pharmacodynamic properties of calcipotriene/betamethasone dipropionate foam. The results of the key randomised clinical studies investigating the efficacy, including patients’ quality of life and safety of the foam versus ointment, gel and either active ingredient in foam vehicle are presented. In addition, the results of a study on maintenance treatment with calcipotriene/betamethasone dipropionate foam as well as reports on real-world use of this medicine in patients with psoriasis, are discussed.